"The Churches overtook politics". The contribution of religious factors and faith-based initiatives to Polish-German reconciliation - Kulska, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
More than half-century long process of reconciliation between Poland and Germany can be recognized as one the most exceptional contemporary examples of the rebuilding of relations both socially and politically. The fact that the reconciliation process between "eternal enemies", Poland and Germany, succeeded is considered in metaphysical categories a "miracle of reconciliation". The essence of this process was well summarized in 2015 in the Common Statement of the President of Poland Andrzej Duda and the President of Germany Joachim Gauck in the words "the Churches overtook politics".
Keywords: reconciliation; forgiveness, guilt; polish-german relationships; civil society